The Impact of COVID-19 Pandemic on Economic Convergence Between Developed and Developing Nations - Sabas , Lucile; Peprah, Williams Kwasi; Troy, Carmelita; Sahly, Quentin (International Journal of Economics and Financial Issues, 2025)
This study investigates convergence between developed and developing countries' GDP during the pre-COVID-19 era (1960–2019) and post-COVID-19 era (2020–2023) using World Bank data and the Augmented Dickey-Fuller (ADF) test. For the pre-COVID period, results show no significant convergence, with an ADF statistic of -1.78 and a p-value of 0.39, likely due to disparities in industrialization and governance. Similarly, post-COVID results (ADF statistic -1.2, p-value 0.67) also suggest no convergence, possibly exacerbated by pandemic-related challenges. The study highlights that structural barriers and the pandemic have hindered economic convergence.